2017
DOI: 10.1016/j.jtumed.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles with antimicrobial and anti-adherence activities against multidrug-resistant isolates from Acinetobacter baumannii

Abstract: Objectives The spread of multidrug-resistant pathogens poses a major health threat. Silver nanoparticles represent a new-class of antimicrobial agents. The aim of this study is the microbial synthesis of silver nanoparticles and the evaluation of their antimicrobial and antibiofilm activities. Methods Silver nanoparticles were synthesized using cell free supernatants of Acinetobacter baumannii . Silver nanoparticles were characterized by parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
7
21
0
Order By: Relevance
“…The SEM examination ( Figure 1 E) showed a homogeneous particle distribution with a roughly spherical geometry. The various sizes may result from the different time intervals when reduction was accomplished, which is in accordance with a previous study that was performed with cell-free supernatants of Acinetobacter baumannii [ 27 ]. The sizes and shapes of metal NPs are affected by various factors, including pH, time of incubation, precursor concentration, reductant concentration, temperature, and method of preparation [ 24 ].…”
Section: Resultssupporting
confidence: 88%
“…The SEM examination ( Figure 1 E) showed a homogeneous particle distribution with a roughly spherical geometry. The various sizes may result from the different time intervals when reduction was accomplished, which is in accordance with a previous study that was performed with cell-free supernatants of Acinetobacter baumannii [ 27 ]. The sizes and shapes of metal NPs are affected by various factors, including pH, time of incubation, precursor concentration, reductant concentration, temperature, and method of preparation [ 24 ].…”
Section: Resultssupporting
confidence: 88%
“…Antibacterial activity of silver NPs were evaluated by many previous studies [30,31], but fewer studies focused on the anti-biofilm activity of SNPs such as [32,33], and the comparative effect of both types (chemical and biological SNPs). Silver NPs were recorded to be anti-biofilm agents which were effective against biofilm bacteria formation, and were also most effective against multi-drug resistant bacteria, resulting from biofilm formation to solve most serious problem to worldwide public health [28,34,35]. Herein, the antimicrobial activity of chemo and biosynthesized SNPs on S. fonticola and Pantoea sp.…”
Section: Antimicrobial Effects Of Silver Nps On Biofilm Bacteriamentioning
confidence: 99%
“…The consequences of these drug resistant infections would cost the world up to 100 trillion USD [20]. Research and development of new antibiotics are among the major interventions with a view to prevent and control the spread of AMR [3], however, several studies have suggested that AgNPs can be used in combating infections caused by MDR bacterial strains [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%